TiO2 / polyaniline organic-inorganic hybrid composite photoanode and preparation method thereof
Through the design of TiO2/polyaniline organic and inorganic hybrid composite photoelectric anode, the problems of high cost, high risk and low photoelectric conversion efficiency in drug wastewater treatment are solved, low-cost and efficient photoelectric conversion and long-term stability are achieved, and the Its application prospects in the fields of solar cells and photoelectric catalysis.
Patent Information
- Application Number
- CN202411540178.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-07
AI Technical Summary
The existing drug wastewater treatment technology has problems such as high cost, high risk of chemical reagents, low photoelectric conversion efficiency and poor material stability, especially in the preparation of complex and moisture-prone aerogel materials and photoelectric integrated catalytic electrodes.
Using TiO2/polyaniline organic and inorganic hybrid composite photoanode, the combination of stainless steel sheet substrate and TiO2/polyaniline composite film layer is used to enhance the binding force using film forming additives to form a smooth and flat surface, and improve it through specific preparation methods. Its photoelectric conversion efficiency.
It has achieved photoelectric conversion effects with low cost, low risk of chemical reagents, enhanced visible light absorption capacity, improved charge separation efficiency, and improved long-term stability. It is suitable for solar cells and photoelectric catalysis fields.
Smart Images

Figure CN119263411A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental chemistry and photoelectrocatalysis, and in particular to a TiO2 / polyaniline organic-inorganic hybrid composite photoanode and a preparation method thereof. Background Art
[0002] At present, the research and development and production of pharmaceutical companies are booming unprecedentedly. Pharmaceutical wastewater has high pollutant content, high toxicity, poor biodegradability, and high salt content. Pharmaceutical wastewater that is discharged without treatment or before treatment meets standards will pose a potential threat to the health of organisms and the environment.
[0003] The main methods for treating pharmaceutical wastewater are physical, chemical oxidation and biological. Although the physical method is simple to operate and low in cost, it is only used to separate macroscopic particles in wastewater and is mostly used for pretreatment. Although the biological method has good degradation effect, it is easily affected by the concentration of pollutants and has disadvantages such as high cost. The chemical method is a wastewater treatment method that changes the chemical or physical properties of pollutants in wastewater through chemical reactions to remove pollutants. Among them, advanced oxidation technology (AOPs) is a physical-chemical combination process that is easy to control, has a wide range of applications, and has no secondary pollution. For example, patent CN201911227040.9 discloses an aerogel material and its preparation method, a catalyst sulfonamide drug wastewater degradation method and application. This invention uses graphene oxide aqueous dispersion and hydrazine hydrate aqueous solution, which can be recycled and reused after simple extrusion to avoid secondary pollution to the environment. However, the aerogel material itself is large in volume, susceptible to moisture and flammable, and has high requirements for the storage environment; patent CN202310040260.0 discloses the preparation of a photoelectric integrated catalytic electrode and its application in the degradation of antiviral drug wastewater. This method prepares a CMO electrocatalytic electrode and a WCN photocatalytic electrode, and places a nickel foam between them to form a composite catalytic electrode with a sandwich structure. Although this invention has a high degradation rate and has certain sustainable utilization, its preparation process is complicated and costly. Dangerous chemical reagents will be used during the experiment, and because of its unique structure, the contact area between the material and water will increase, which will affect the photoelectric conversion efficiency to a certain extent.
[0004] Therefore, a TiO2 / polyaniline organic-inorganic hybrid composite photoanode and a preparation method thereof are needed to improve the above-mentioned problems. Summary of the invention
[0005] The object of the present invention is to provide a TiO2 / polyaniline organic-inorganic hybrid composite photoanode and a preparation method thereof to solve the problems raised in the above background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A TiO2 / polyaniline organic-inorganic hybrid composite photoelectric anode includes: the composite photoelectric anode uses a stainless steel sheet as a substrate, and the surface layer is a TiO2 / polyaniline composite film layer. In the photoelectric anode composite layer, the TiO2 / polyaniline and the stainless steel substrate are combined through the action of a film-forming aid, and the surface of the composite photoelectric anode is smooth and flat.
[0008] As a preferred solution of the present invention, the thickness of the stainless steel substrate is 0.5-1 mm, the thickness of the TiO2 / polyaniline composite layer is 700-800 nm, and the particle size of the TiO2 / polyaniline is 20-30 nm.
[0009] A method for preparing a TiO2 / polyaniline organic-inorganic hybrid composite photoanode comprises the following steps:
[0010] Step 1, add a certain amount of rectified aniline, a certain amount of hydrochloric acid solution and a certain amount of PTC into a 250 ml three-necked flask in sequence, and stir it at a suitable speed in an ice water bath environment;
[0011] Step 2, add a certain amount of ammonium persulfate and a functional group reagent mixed solution dropwise into a three-necked flask, and add it dropwise into the three-necked flask for a certain period of time. At this time, the solution is blue-black, and continue to stir in an ice-water bath environment for a certain period of time before stopping the reaction;
[0012] Step 3, after the reaction, washing and filtering are performed in sequence with hydrochloric acid, anhydrous ethanol and a large amount of distilled water, the filtered product is placed in a vacuum drying oven for drying, and then ground and sieved to obtain TiO2 / polyaniline powder;
[0013] Step 4, adding a certain amount of catalyst to a certain amount of ethanol-water solution, then adding a certain concentration of Nafion solution, and stirring for a certain period of time;
[0014] Step 5: After stirring, evenly drip the solution onto the surface of the dry stainless steel sheet, dry it in a vacuum drying oven at a specific temperature for 12 hours, and take it out for use;
[0015] Step 6: Weigh a certain amount of target pollutants, insert the polyaniline / TiO2 powder photoanode and the stainless steel cathode into the target pollutant solution, and set different voltages, times, plate distances and energy sources.
[0016] As a preferred solution of the present invention, in step 1, 1-5 ml of the distilled aniline is taken, the molar ratio of hydrochloric acid solution to aniline is 1:1-6, the molar ratio of PTC to aniline is 1:1-60, and the ice water bath environment is best at -5-0°C.
[0017] As a preferred embodiment of the present invention, the preparation method of the PTC is as follows: 0.1 mol of inorganic titanium salt is dissolved in 400 ml of distilled water, and then ammonia water is added dropwise to adjust the pH of the solution to 7 to form a titanium hydroxide precipitate, the precipitate is allowed to stand overnight, layered, washed, and prepared into a 0.2 mol / L solution, and then 340 g of a 30% hydrogen peroxide solution and 1 L of distilled water are added to the solution, and the reaction is carried out at 100° C. for 1 hour.
[0018] As a preferred solution of the present invention, in step 2, 100 ml of a mixed solution of ammonium persulfate and a functional group reagent is measured, wherein the molar ratio of ammonium persulfate to aniline is 1:1-10, and the molar ratio of the functional group reagent to PTC is 1:1-10. After the mixed solution is added dropwise, the reaction is stopped after stirring for 0.5-10 hours in an ice water bath.
[0019] As a preferred solution of the present invention, in step 4, 1-100 mg of catalyst is taken, 1-10 ml of ethanol aqueous solution (water and ethanol volume ratio is 1:3) is taken, 1-100 ul of Nafion solution with a concentration of 5% is taken, and the sufficient stirring time is 1-24 h.
[0020] As a preferred embodiment of the present invention, in step 6, the target pollutant is acetaminophen, the concentration of the target pollutant solution is 10-100 mg / L and 1000 ml of the solution is taken, wherein the voltage is set to 5V-30V, the time is 0.5h-8h, and the plate distance is 1cm-10cm.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. In the present invention, the TiO2 / polyaniline composite photoanode has low cost, low chemical reagent hazard, less harm to the environment and has enhanced visible light absorption, which can improve the absorption capacity of the composite anode in the visible light region and fully improve the utilization efficiency of solar energy. In addition, the interfacial interaction between TiO2 and polyaniline may help promote charge separation and provide a more effective charge transfer channel, reduce charge recombination loss, and thus improve the photoelectric conversion efficiency.
[0023] 2. In the present invention, polyaniline can protect TiO2 from the influence of the storage environment to a certain extent, thereby improving the long-term stability of the photoanode.
[0024] 3. In the present invention, the hybrid composite photoanode has a wider application prospect in the fields of solar cells, photoelectrocatalysis, etc., and provides new ideas and material selections for the development of related technologies. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1This is a performance diagram of degrading 10 mg / L acetaminophen in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In the description of the present application, it should be noted that the terms used herein are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present application. For ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The technology, methods and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but in appropriate cases, the technology, methods and equipment should be regarded as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as merely exemplary, rather than as a limitation. Therefore, other examples of the exemplary embodiments may have different values. It should be noted that similar numbers and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further discussed in subsequent drawings.
[0028] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable under appropriate circumstances, so that the embodiments of the present application can be implemented in an order other than those illustrated or described here, and the objects distinguished by "first", "second", etc. are generally of one type, and the number of objects is not limited. For example, the first object can be one or more. In addition, "and / or" in the specification and claims represents at least one of the connected objects, and the character " / " generally indicates that the objects associated with each other are in an "or" relationship.
[0029] It should be noted that, in the description of the present application, the orientation or positional relationship indicated by terms such as "front, back, up, down, left, right", "lateral, vertical, perpendicular, horizontal" and "top, bottom" are usually based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description. Unless otherwise stated, these orientation words do not indicate or imply that the device or element referred to must have a specific orientation or be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the scope of protection of the present application; the orientation words "inside and outside" refer to the inside and outside relative to the contour of each component itself.
[0030] It should be noted that, in the present application, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises one..." does not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be noted that the scope of the method and device in the embodiment of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0031] See also Figure 1 , the present invention provides a technical solution:
[0032] A TiO2 / polyaniline organic-inorganic hybrid composite photoelectric anode includes: the composite photoelectric anode uses a stainless steel sheet as a substrate, and the surface layer is a TiO2 / polyaniline composite film layer. In the photoelectric anode composite layer, the TiO2 / polyaniline and the stainless steel substrate are combined through the action of a film-forming aid, and the surface of the composite photoelectric anode is smooth and flat.
[0033] As an example of the present invention, the thickness of the stainless steel substrate is 0.5-1 mm, the thickness of the TiO2 / polyaniline composite layer is 700-800 nm, and the particle size of the TiO2 / polyaniline is 20-30 nm.
[0034] A method for preparing a TiO2 / polyaniline organic-inorganic hybrid composite photoanode comprises the following steps:
[0035] Step 1, add a certain amount of rectified aniline, a certain amount of hydrochloric acid solution and a certain amount of PTC into a 250 ml three-necked flask in sequence, and stir it at a suitable speed in an ice water bath environment;
[0036] Step 2, add a certain amount of ammonium persulfate and a functional group reagent mixed solution dropwise into a three-necked flask, and add it dropwise into the three-necked flask for a certain period of time. At this time, the solution is blue-black, and continue to stir in an ice-water bath environment for a certain period of time before stopping the reaction;
[0037] Step 3, after the reaction, washing and filtering are performed in sequence with hydrochloric acid, anhydrous ethanol and a large amount of distilled water, the filtered product is placed in a vacuum drying oven for drying, and then ground and sieved to obtain TiO2 / polyaniline powder;
[0038] Step 4, adding a certain amount of catalyst to a certain amount of ethanol-water solution, then adding a certain concentration of Nafion solution, and stirring for a certain period of time;
[0039] Step 5: After stirring, evenly drip the solution onto the surface of the dry stainless steel sheet, dry it in a vacuum drying oven at a specific temperature for 12 hours, and take it out for use;
[0040] Step 6: Weigh a certain amount of target pollutants, insert the TiO2 / polyaniline powder photoanode and the stainless steel cathode into the target pollutant solution, and set different voltages, times, plate distances and energy sources.
[0041] As an example of the present invention, in step 1, 1-5 ml of aniline after distillation is taken, the molar ratio of hydrochloric acid solution to aniline is 1:1-6, the molar ratio of PTC to aniline is 1:1-60, and the ice water bath environment is best at -5-0°C.
[0042] As an example of the present invention, the preparation method of PTC is as follows: 0.1 mol of inorganic titanium salt is dissolved in 400 ml of distilled water, and then ammonia water is added dropwise to adjust the pH of the solution to 7 to form a titanium hydroxide precipitate, the precipitate is allowed to stand overnight, layered, washed, and prepared into a 0.2 mol / L solution, and then 340 g of 30% hydrogen peroxide solution and 1 L of distilled water are added to the solution, and the reaction is carried out at 100°C for 1 hour.
[0043] As an example of the present invention, in step 2, 100 ml of a mixed solution of ammonium persulfate and a functional group reagent is measured, wherein the molar ratio of ammonium persulfate to aniline is 1:1-10, and the molar ratio of the functional group reagent to PTC is 1:1-10. After the mixed solution is added dropwise, the reaction is stopped after stirring for 0.5-10 hours in an ice water bath.
[0044] As an example of the present invention, in step 4, 1-100 mg of catalyst is taken, 1-10 ml of ethanol aqueous solution (water and ethanol volume ratio is 1:3) is taken, 1-100 ul of Nafion solution with a concentration of 5% is taken, and the sufficient stirring time is 1-24 h.
[0045] As an example of the present invention, in step 6, the target pollutant is acetaminophen, the concentration of the target pollutant solution is 10-100 mg / L and 1000 ml of the solution is taken, wherein the voltage is set to 5V-30V, the time is 0.5h-8h, and the plate distance is 1cm-10cm.
[0046] Example 1
[0047] 4 ml of distilled aniline, 2 mol of hydrochloric acid solution and 4 mol of PTC were added to a 250 ml three-necked flask in sequence, and stirred at a suitable speed for 30 min in an ice-water bath at 0°C. 100 ml of (1 mol of ammonium persulfate + 1 mol of hydroxylamine hydrochloride) solution was added dropwise to the three-necked flask within 20 min. At this time, the solution was blue-black. Stirring was continued at 0°C, and the reaction was stopped after retiming for 4 hours. After the reaction, 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water were used to wash and filter in sequence, and the filtered material was placed in a vacuum drying oven at 60°C and dried for 12 hours. TiO2 / polyaniline powder was obtained by grinding and sieving.
[0048] Add 10mg TiO2 / polyaniline powder to 2ml ethanol-water solution (volume ratio of water to ethanol is 1:3), then add 20ul 5% Nafion solution, stir thoroughly for 12h, and after stirring, evenly drip the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm, dry it in a vacuum oven at 60℃ and take it out for use. Insert the polyaniline / TiO2 powder photoanode and the stainless steel cathode into the acetaminophen solution, set the voltage to 25V, the plate distance to 10cm, and turn on the light source, and the photocatalytic time is 2 hours.
[0049] Example 2
[0050] 5 ml of distilled aniline, 1 mol of hydrochloric acid solution and 3 mol of PTC were added to a 250 ml three-necked flask in sequence, and stirred at an appropriate speed for 30 min in an ice-water bath at -5°C. 100 ml of (10 mol of ammonium persulfate + 10 mol of hydroxylamine hydrochloride) solution was added dropwise to the three-necked flask within 20 min. At this time, the solution was blue-black. Stirring was continued in an ice-water bath at -5°C, and the reaction was stopped after retiming for 0.5 h. After the reaction, 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water were used to wash and filter in sequence, and the filtered material was placed in a vacuum drying oven at 60°C and dried for 12 h. TiO2 / polyaniline powder was obtained by grinding and sieving.
[0051] Add 1mg TiO2 / polyaniline powder to 1ml ethanol-water solution (volume ratio of water to ethanol is 1:1), then add 1ul 5% Nafion solution, stir thoroughly for 1h, and after stirring, evenly drop the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm, dry it in a vacuum drying oven at 60℃ and take it out for use. Insert the polyaniline / TiO2 powder photoanode and the stainless steel cathode into the acetaminophen solution, set the voltage to 5V, the plate distance to 10cm, and turn on the light source, the photocatalytic time is 0.5 hours.
[0052] Example 3
[0053] 1 ml of rectified aniline, 6 mol of hydrochloric acid solution and 60 mol of PTC were added to a 250 ml three-necked flask in sequence, and stirred at a suitable speed for 30 min in an ice-water bath at 0°C. 100 ml of (1 mol of ammonium persulfate + 1 mol of hydroxylamine hydrochloride) solution was added dropwise to the three-necked flask within 20 min. At this time, the solution was blue-black. Stirring was continued in an ice-water bath at 0°C, and the reaction was stopped after retiming for 10 h. After the reaction, 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water were used to wash and filter in sequence, and the filtered material was placed in a vacuum drying oven at 60°C and dried for 12 h. TiO2 / polyaniline powder was obtained by grinding and sieving.
[0054] Add 100mg TiO2 / polyaniline powder to 10ml ethanol-water solution (volume ratio of water to ethanol is 1:10), then add 100ul 5% Nafion solution, stir thoroughly for 24h, and after stirring, evenly drip the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm, dry it in a vacuum oven at 60℃ and take it out for use. Insert the TiO2 / polyaniline powder photoanode and the stainless steel cathode into the acetaminophen solution, set the voltage to 30V, the plate distance to 1cm, and turn on the light source, the photocatalytic time is 8 hours.
[0055] Example 4
[0056] 2 ml of distilled aniline, 5 mol of hydrochloric acid solution and 50 mol of PTC were added to a 250 ml three-necked flask in sequence, and stirred at a suitable speed for 30 min in an ice-water bath at -4 ° C. 100 ml of (5 mol of ammonium persulfate + 5 mol of hydroxylamine hydrochloride) solution was added dropwise to the three-necked flask within 20 min. At this time, the solution was blue-black. Stirring was continued in an ice-water bath at -4 ° C. The reaction was stopped after retiming for 5 hours. After the reaction, 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water were used to wash and filter in sequence, and the filtered material was placed in a vacuum drying oven at 60 ° C. and dried for 12 h. TiO2 / polyaniline powder was obtained by grinding and sieving.
[0057] Add 50mg TiO2 / polyaniline powder to 5ml ethanol-water solution (volume ratio of water to ethanol is 1:5), then add 50ul 5% Nafion solution, stir thoroughly for 12h, and after stirring, evenly drip the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm, dry it in a vacuum oven at 60℃ and take it out for use. Insert the TiO2 / polyaniline powder photoanode and the stainless steel cathode into the acetaminophen solution, set the voltage to 15V, the plate distance to 5cm, and turn on the light source, and the photocatalytic time is 4 hours.
[0058] Example 5
[0059] 3 ml of distilled aniline, 3 mol of hydrochloric acid solution and 25 mol of PTC were added to a 250 ml three-necked flask in sequence, and stirred at a suitable speed for 30 min in an ice-water bath at -3°C. 100 ml of (3 mol of ammonium persulfate + 3 mol of hydroxylamine hydrochloride) solution was added dropwise to the three-necked flask within 20 min. At this time, the solution was blue-black. Stirring was continued in an ice-water bath at -3°C, and the reaction was stopped after 7 h. After the reaction, 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water were used to wash and filter in sequence, and the filtered material was placed in a vacuum drying oven at 60°C and dried for 12 h. TiO2 / polyaniline powder was obtained by grinding and sieving.
[0060] Add 75mg TiO2 / polyaniline powder to 7ml ethanol-water solution (volume ratio of water to ethanol is 1:7), then add 75ul 5% Nafion solution, stir thoroughly for 18h, and after stirring, evenly drip the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm, dry it in a vacuum oven at 60℃ and take it out for use. Insert the TiO2 / polyaniline powder photoanode and the stainless steel cathode into the acetaminophen solution, set the voltage to 20V, the plate distance to 8cm, and turn on the light source, and the photocatalytic time is 6 hours.
[0061] Example 6
[0062] 5 ml of rectified aniline, 4 mol of hydrochloric acid solution and 33 mol of PTC were added to a 250 ml three-necked flask in sequence, and stirred at a suitable speed for 30 min in an ice-water bath at -2°C. 100 ml of (6 mol of ammonium persulfate + 3 mol of methanol + 3 mol of hydrogen peroxide) solution was added dropwise to the three-necked flask within 20 min. At this time, the solution was blue-black. Stirring was continued in an ice-water bath at -2°C, and the reaction was stopped after retiming for 3 hours. After the reaction, 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water were used to wash and filter in sequence, and the filtered material was placed in a vacuum drying oven at 60°C and dried for 12 h. TiO2 / polyaniline powder was obtained by grinding and sieving.
[0063] Add 25mg TiO2 / polyaniline powder to 4ml ethanol-water solution (volume ratio of water to ethanol is 1:4), then add 25ul 5% Nafion solution, stir thoroughly for 8h, and evenly drip the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm. Dry it in a vacuum oven at 60℃ and take it out for use. Insert the TiO2 / polyaniline powder photoanode and the stainless steel cathode into the acetaminophen solution, set the voltage to 15V, the plate distance to 4cm, and turn on the light source. The photocatalytic time is 3 hours.
[0064] Example 7
[0065] 5 ml of distilled aniline, 2 mol of hydrochloric acid solution and 15 mol of PTC were added to a 250 ml three-necked flask in sequence, and stirred at a suitable speed for 30 min in an ice-water bath at -1°C. 100 ml of (7 mol of ammonium persulfate + 2 mol of hydrazine hydrate + 3 mol of methylamine) solution was added dropwise to the three-necked flask within 20 min. At this time, the solution was blue-black. Stirring was continued in an ice-water bath at -1°C, and the reaction was stopped after retiming for 4 hours. After the reaction, 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water were used to wash and filter in sequence, and the filtered material was placed in a vacuum drying oven at 60°C and dried for 12 hours. TiO2 / polyaniline powder was obtained by grinding and sieving.
[0066] Add 35mg TiO2 / polyaniline powder to 6ml ethanol-water solution (volume ratio of water to ethanol is 1:6), then add 45ul 5% Nafion solution, stir thoroughly for 11h, and after stirring, evenly drip the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm, dry it in a vacuum oven at 60℃ and take it out for use. Insert the TiO2 / polyaniline powder photoanode and the stainless steel cathode into the acetaminophen solution, set the voltage to 10V, the plate distance to 6cm, and turn on the light source, and the photocatalytic time is 6 hours.
[0067] Example 8
[0068] 3 ml of rectified aniline, 6 mol of hydrochloric acid solution and 28 mol of PTC were added to a 250 ml three-necked flask in sequence, and stirred at a suitable speed for 30 min in an ice-water bath at 0°C. 100 ml of (4 mol of ammonium persulfate + 1 mol of hydroxylamine + 2 mol of methanol + 3 mol of methylamine) solution was added dropwise to the three-necked flask within 20 min. At this time, the solution was blue-black. Stirring was continued in an ice-water bath at 0°C, and the reaction was stopped after retiming for 6.5 h. After the reaction, 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water were used to wash and filter in sequence, and the filtered material was placed in a vacuum drying oven at 60°C and dried for 12 h. The polyaniline / TiO2 powder was obtained by grinding and sieving.
[0069] Add 65mg TiO2 / polyaniline powder to 8ml ethanol-water solution (volume ratio of water to ethanol is 1:9), then add 85ul 5% Nafion solution, stir thoroughly for 15h, and after stirring, evenly drip the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm, dry it in a vacuum oven at 60℃ and take it out for use. Insert the TiO2 / polyaniline powder photoanode and the stainless steel cathode into the acetaminophen solution, set the voltage to 20V, the plate distance to 7cm, and turn on the light source, the photocatalytic time is 7.5 hours.
[0070] Example 9
[0071] 2 ml of distilled aniline, 1 mol of hydrochloric acid solution and 5 mol of PTC were added to a 250 ml three-necked flask in sequence, and stirred at a suitable speed for 30 min in an ice-water bath at 0°C. 100 ml of (9 mol of ammonium persulfate + 1 mol of hydroxylamine sulfate) solution was added dropwise to the three-necked flask within 20 min. At this time, the solution was blue-black. Stirring was continued at -3°C, and the reaction was stopped after 8.5 h. After the reaction, 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water were used to wash and filter in sequence, and the filtered material was placed in a vacuum drying oven at 60°C and dried for 12 h. TiO2 / polyaniline powder was obtained by grinding and sieving.
[0072] Add 86mg TiO2 / polyaniline powder to 9ml ethanol-water solution (volume ratio of water to ethanol is 1:9), then add 95ul 5% Nafion solution, stir thoroughly for 19h, and after stirring, evenly drip the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm, dry it in a vacuum oven at 60℃ and take it out for use. Insert the TiO2 / polyaniline powder photoanode and the stainless steel cathode into the acetaminophen solution, set the voltage to 15V, the plate distance to 10cm, and turn on the light source, the photocatalytic time is 5.5 hours.
[0073] Example 10
[0074] 1 ml of rectified aniline, 2 mol of hydrochloric acid solution and 45 mol of PTC were added to a 250 ml three-necked flask in sequence, and stirred at a suitable speed for 30 min in an ice-water bath at 0°C. 100 ml of (2 mol of ammonium persulfate + 1 mol of hydrazine hydrate + 2 mol of methylamine) solution was added dropwise to the three-necked flask within 20 min. At this time, the solution was blue-black. Stirring was continued in an ice-water bath at 0°C, and the reaction was stopped after retiming for 9.5 h. After the reaction, 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water were used to wash and filter in sequence, and the filtered material was placed in a vacuum drying oven at 60°C and dried for 12 h. TiO2 / polyaniline powder was obtained by grinding and sieving.
[0075] Add 80mg TiO2 / polyaniline powder to 8ml ethanol-water solution (volume ratio of water to ethanol is 1:7), then add 80ul 5% Nafion solution, stir thoroughly for 13h, after stirring, evenly drop the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm, dry it in a vacuum oven at 60℃ and take it out for use. Insert the TiO2 / polyaniline powder photoanode and the stainless steel cathode into the acetaminophen solution, set the voltage to 15V, the plate distance to 5cm, and turn on the light source, the photocatalytic time is 4 hours.
[0076] Comparative Example 1
[0077] 4 ml of distilled aniline, 2 mol of hydrochloric acid solution and 4 mol of PTC were added to a 250 ml three-necked flask in sequence, and stirred at a suitable speed for 30 min in an ice-water bath at 0°C. 100 ml of (1 mol of ammonium persulfate + 1 mol of hydroxylamine hydrochloride) solution was added dropwise to the three-necked flask within 20 min. At this time, the solution was blue-black. Stirring was continued at 0°C, and the reaction was stopped after retiming for 4 hours. After the reaction, 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water were used to wash and filter in sequence, and the filtered material was placed in a vacuum drying oven at 60°C and dried for 12 hours. TiO2 / polyaniline powder was obtained by grinding and sieving.
[0078] Add 10mg TiO2 / polyaniline powder to 2ml ethanol-water solution (volume ratio of water to ethanol is 1:3), then add 20ul 5% Nafion solution, stir thoroughly for 12h, and evenly drip the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm. Dry it in a vacuum oven at 60℃ and take it out for use. Insert the TiO2 / polyaniline powder photoanode and the stainless steel cathode into the acetaminophen solution together, do not set the voltage, only set the plate distance to 10cm, and turn on the light source, and the photocatalytic time is 2 hours.
[0079] Comparative Example 2
[0080] 4 ml of distilled aniline, 2 mol of hydrochloric acid solution and 4 mol of PTC were added to a 250 ml three-necked flask in sequence, and stirred at a suitable speed for 30 min in an ice-water bath at 0°C. 100 ml of (1 mol of ammonium persulfate + 1 mol of hydroxylamine hydrochloride) solution was added dropwise to the three-necked flask within 20 min. At this time, the solution was blue-black. Stirring was continued at 0°C, and the reaction was stopped after retiming for 4 hours. After the reaction, 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water were used to wash and filter in sequence, and the filtered material was placed in a vacuum drying oven at 60°C and dried for 12 hours. TiO2 / polyaniline powder was obtained by grinding and sieving.
[0081] Add 10mg TiO2 / polyaniline powder to 2ml ethanol-water solution (volume ratio of water to ethanol is 1:3), then add 20ul 5% Nafion solution, stir thoroughly for 12h, and after stirring, evenly drip the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm, dry it in a vacuum oven at 60℃ and take it out for use. Insert the TiO2 / polyaniline powder photoanode and the stainless steel cathode into the acetaminophen solution, set the voltage to 25V, keep the plate distance to 10cm, do not turn on the light source, and the electrocatalytic time is 2 hours.
[0082] Comparative Example 3
[0083] Add 4 mol PTC into a 250 ml three-necked flask, stir and mix at a suitable speed in an ice-water bath at 0°C for 30 minutes, then take 1 mol hydroxylamine hydrochloride solution and add it dropwise into the three-necked flask within 20 minutes. At this time, the solution is blue-black. Continue stirring at 0°C, and stop the reaction after retiming for 4 hours. After the reaction, use 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water to wash and filter in turn. Place the filtered material in a vacuum drying oven at 60°C and dry it for 12 hours. Grind and sieve to obtain TiO2 powder.
[0084] Add 10mg TiO2 powder to 2ml ethanol-water solution (volume ratio of water to ethanol is 1:3), then add 20ul 5% Nafion solution, stir thoroughly for 12h, and after stirring, evenly drip the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm, dry it in a vacuum drying oven at 60℃ and take it out for use. Insert the TiO2 powder photoanode and the stainless steel cathode into the acetaminophen solution, set the voltage to 25V, the plate distance to 10cm, and turn on the light source, and the photocatalytic time is 2 hours.
[0085] Comparative Example 4
[0086] 4 ml of rectified aniline and 2 mol of hydrochloric acid solution are added to a 250 ml three-necked flask in sequence, and stirred and mixed at a suitable speed for 30 minutes in an ice-water bath environment at 0°C. 1 mol of ammonium persulfate solution is added dropwise to the three-necked flask, and the solution is added dropwise to the three-necked flask within 20 minutes. At this time, the solution is blue-black, and stirring is continued at 0°C. The reaction is stopped after retiming for 4 hours. After the reaction, 400 ml of 0.36 mol / L hydrochloric acid, 200 ml of anhydrous ethanol and a large amount of distilled water are used to wash and filter in sequence, and the filtered material is placed in a vacuum drying oven at 60°C and dried for 12 hours, and the polyaniline powder is obtained by grinding and sieving.
[0087] Add 10mg of polyaniline powder to 2ml of ethanol-water solution (volume ratio of water to ethanol is 1:3), then add 20ul5% Nafion solution, stir thoroughly for 12h, and after stirring, evenly drip the solution onto the surface of a dry stainless steel sheet with a length and width of 10*5cm, dry it in a vacuum oven at 60℃ and take it out for use. Insert the polyaniline powder photoanode and the stainless steel cathode into the acetaminophen solution, set the voltage to 25V, the plate distance to 10cm, and turn on the light source, and the photocatalytic time is 2 hours.
[0088] Results Analysis
[0089] As can be seen from the figure, the degradation efficiency of single PANI in Comparative Example 4 is 71.5%, the degradation efficiency of photocatalysis in Comparative Example 1 is 82.5%, followed by Comparative Example 2 with an electrocatalytic degradation efficiency of 84.2%, and the degradation efficiency of single TiO2 in Comparative Example 3 is 86.2%. The highest degradation efficiency is 98.2% for the photoelectrocatalytic TiO2 / polyaniline composite anode in Example 1. The reason for the different degradation efficiencies of Comparative Example 1, Comparative Example 2 and Example 1 may be that photocatalysis directly uses light energy to drive the reaction, which may be affected by factors such as light source stability and uneven light intensity distribution, while electrocatalysis relies on external power source energy, which may be affected by factors such as electrode materials and reaction conditions, and there is a problem of low energy conversion efficiency. Photoelectrocatalysis combines the advantages of photocatalysis and electrocatalysis, and the interaction between TiO2 and polyaniline provides more active sites and increases the contact opportunities between reactants and catalysts. Both also promote charge separation and transfer, reduce the overpotential of the reaction, and improve the reaction rate and selectivity. At the same time, it promotes the separation and transmission of photogenerated electrons and holes, allowing more photogenerated electrons and holes to participate in the redox reaction, thereby improving the efficiency of photocatalysis. The reason for the different degradation efficiencies among Comparative Examples 3, 4 and Example 1 is that the composite anode generally has better chemical stability and physical stability than a single anode, and can better adapt to changes in various environmental factors. This stability helps maintain the long-term high-efficiency performance of the anode, thereby improving the degradation efficiency.
[0090] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A TiO2 / polyaniline organic-inorganic hybrid composite photoanode, comprising: The composite photoanode has a stainless steel sheet as a substrate and a TiO2 / polyaniline composite film layer as a surface layer. The TiO2 / polyaniline in the photoanode composite layer is combined with the stainless steel substrate through the action of a film-forming aid, and the surface of the composite photoanode is smooth and flat.
2. The TiO2 / polyaniline organic-inorganic hybrid composite photoanode according to claim 1, characterized in that: The thickness of the stainless steel substrate is 0.5-1 mm, the thickness of the TiO2 / polyaniline composite layer is 700-800 nm, and the particle size of the TiO2 / polyaniline is 20-30 nm.
3. A method for preparing a TiO2 / polyaniline organic-inorganic hybrid composite photoanode, characterized in that: The following steps are involved: Step 1, add a certain amount of rectified aniline, a certain amount of hydrochloric acid solution and a certain amount of PTC into a 250 ml three-necked flask in sequence, and stir it at a suitable speed in an ice water bath environment; Step 2, add a certain amount of ammonium persulfate and a functional group reagent mixed solution dropwise into a three-necked flask, and add it dropwise into the three-necked flask for a certain period of time. At this time, the solution is blue-black, and continue to stir in an ice-water bath environment for a certain period of time before stopping the reaction; Step 3, after the reaction, washing and filtering are performed in sequence with hydrochloric acid, anhydrous ethanol and a large amount of distilled water, the filtered product is placed in a vacuum drying oven for drying, and then ground and sieved to obtain TiO2 / polyaniline powder; Step 4, adding a certain amount of catalyst to a certain amount of ethanol-water solution, then adding a certain concentration of Nafion solution, and stirring for a certain period of time; Step 5: After stirring, evenly drip the solution onto the surface of the dry stainless steel sheet, dry it in a vacuum drying oven at a specific temperature for 12 hours, and take it out for use; Step 6: Weigh a certain amount of target pollutants, insert the TiO2 / polyaniline powder photoanode and the stainless steel cathode into the target pollutant solution, and set different voltages, times, plate distances and energy sources.
4. The method for preparing a TiO2 / polyaniline organic-inorganic hybrid composite photoanode according to claim 1, characterized in that: In the step 1, 1-5 ml of the aniline after distillation is taken, the molar ratio of the hydrochloric acid solution to the aniline is 1:1-6, the molar ratio of PTC to the aniline is 1:1-60, and the ice water bath environment is optimally -5-0°C.
5. The TiO2 / polyaniline organic-inorganic hybrid composite photoanode and the preparation method thereof according to claim 4, characterized in that: The preparation method of the PTC is as follows: 0.1 mol of inorganic titanium salt is dissolved in 400 ml of distilled water, and then ammonia water is added dropwise to adjust the pH of the solution to 7 to form titanium hydroxide precipitate, the precipitate is allowed to stand overnight, layered, washed, and prepared into a 0.2 mol / L solution, and then 340 g of a 30% by mass hydrogen peroxide solution and 1 L of distilled water are added to the solution, and the reaction is carried out at 100° C. for 1 hour.
6. The TiO2 / polyaniline organic-inorganic hybrid composite photoanode and the preparation method thereof according to claim 1, characterized in that: In the step 2, 100 ml of a mixed solution of ammonium persulfate and a functional group reagent is measured, wherein the molar ratio of ammonium persulfate to aniline is 1:1-10, and the molar ratio of the functional group reagent to PTC is 1:1-10. After the mixed solution is added dropwise, the mixture is stirred in an ice water bath for 0.5-10 h and then the reaction is stopped.
7. The TiO2 / polyaniline organic-inorganic hybrid composite photoanode and the preparation method thereof according to claim 1, characterized in that: In step 4, 1-100 mg of the catalyst is taken, 1-10 ml of the ethanol aqueous solution (the volume ratio of water to ethanol is 1:3) is taken, 1-100 ul of the Nafion solution with a concentration of 5% is taken, and the stirring time is 1-24 h.
8. The TiO2 / polyaniline organic-inorganic hybrid composite photoanode and the preparation method thereof according to claim 1, characterized in that: In step 6, the target pollutant is acetaminophen, the concentration of the target pollutant solution is 10-100 mg / L, and 1000 ml of the solution is taken, wherein the voltage is set to 5V-30V, the time is 0.5h-8h, and the plate distance is 1cm-10cm.
Citation Information
Patent Citations
Aerogel material and preparation method thereof, catalyst, and sulfonamide wastewater degradation method and application thereof
CN110918009A
Preparation of photoelectric integrated catalytic electrode and application of photoelectric integrated catalytic electrode in degradation of antiviral drug wastewater
CN116002817A
Cited By
Method for treating industrial wastewater by electrochemical enhanced hydrolytic acidification
CN120247233A
A method for treating industrial wastewater by electrochemically enhanced hydrolysis and acidification
CN120247233B